USE OF PROFESSIONAL TERMINOLOGY IN THE EDUCATIONAL PROCESS - Tuychieva Saodat Melikuzievna (International Journal on Integrated Education, 2020)
This article discusses the use of professional terminology and the introduction of innovative technologies in the educational process today, the emergence of the term innovation and its place and role in the development of pedagogical thinking. The article discusses the role of "Communication" technology in the formation of oral skills in education and the practical results of its use. It also reveals the principles of developing an innovative environment, methods of organizing innovative activities of all participants in the educational process.